Analisis Pengaruh Kualitas Layanan Internet Banking dan Tingkat Kepuasan Terhadap Loyalitas Nasabah Pada PT Bank Rakyat Indonesia (Persero) Tbk Kantor Cabang Pembantu Jamsostek Jakarta - Huda, Ahmad Nurul; Wahyuni, Sri (Business and Management Review, 2012)
The Internet is an ideal  media to  take any banking activities  due to it has the potential  cost savings. Internet also one of the  media used to  improve services  for the customers  in order to reach  customer loyalty.  The function  not only for giving information, but it also can handle banking transactions anytime and anywhere without being limited by time and distance.  This study  aims to determine  how the  influence of  service  quality of internet banking, customer  satisfaction,  and customer loyalty at Bank Rakyat Indonesia Sub-Branch Jamsostek. Sampling  technique used was  nonprobability  sampling method.  There 105  respondents were given questionnaire. The analysis of data is using SEM analysis (Structural Equation Modeling) with AMOS program.  The results indicated that the variable of service quality of internet banking has positive and significant influence on customer satisfaction. Customer satisfaction has negative significantly correlated with customer loyalty. This result confirms that the service quality of internet banking has no significant direct influence on customer loyalty but it has a significant influence indirectly through customer satisfaction as mediating (intervening variable). Key Words: Internet Banking, Service Quality, Satisfaction, Loyalty.